Identifikasi Kedalaman Pirit dan Kaitannya Terhadap Kesehatan dan Produktivitas Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) ( Studi Kasus di Perkebunan PT Sawit Sumbermas Sarana Tbk ) - Aris Primayuda; Abraham Suriadikusumah; M Amir Solihin (Jurnal Ilmu Tanah dan Lingkungan, 2022)
The pyrite layer (FeS2) characterizes acid sulphate soil. Under oxidized conditions, pyrite produces sulphuric acid that increases acidic soil to very acidic (pH 2-3). This condition is a threat to plantation, including oil palm plantation. Therefore, the management of acid sulphate soil must take into account the depth of pyrite layer. Studies on the identification of pyrite and the use of remote sensing in monitoring plant health are urgently required to optimize oil palm production in acid sulphate soil. In this case study, detailed survey and mapping were performed to measure the depth of pyrite followed by plant health analysis, and production analysis. The results showed that the depth of pyrite layer at the site ranged from 30 cm to over 120 cm from the soil surface. The depth indicated that the 72.40% of the soil was categorized medium pyrite depth (60-120 cm). Furthermore, 484.85 ha was shallow pyrite layer (<60 cm) and deep pyrite layer (>120 cm) covered an area of 163.75 ha. A tendency for a positive linear relationship between pyrite depth, NDVI (normalized difference vegetation index) or plant health, and plant productivity. NDVI values and plant productivity and deeper pyrite depth was identified as shown in higher NDVI values following deeper pyrite layer. Plant productivity on deep pyrite soil was significantly different from the one in medium or shallow pyrite soil. Shallower pyrite layer was followed by lower oil palm production. The productivity has decreased by 39% and 19% in soil with pyrite depths of < 60 cm and 60 cm – 120 cm respectively.